Social Capital and Social Capacity in Rural Ecotourism Development - Iwan Nugroho; Rita Hanafie; Purnawan Dwikora Negara; Sudiyono Sudiyono; Hefifa Rhesa Yuniar (Faculty of Geography, Universitas Gadjah Mada, 2021)
The participation of rural people in ecotourism activity remains the question, whether they genuinely carry the vision of conservation or are forced to engage in meeting economic needs only. This question is fundamental for building better participation and management of ecotourism in rural areas. The research aims to discuss social capital and social capacities to empower ecotourism in rural areas. The study was carried out in the villages of Ngadas and Gombengsari using a survey approach, and employing descriptive and path analysis methods. The results show that social capital for managing ecotourism services demonstrated the functioning of institutions, networking capabilities, monitoring, evaluation, and innovation. Social capacity is related to the regulation of institutional, social, economic, and environmental resources. Social capacity was found more substantial in Gombengsari than Ngadas village. The research is expected to strengthen the study of social capital as a stock/sink and its relationship with sustainability.